Changing content plan structure of companies operating in Russia and represented on VK - L. G. Akhmaeva; A. I. Eremeeva (Цифровая социология)
The article identifies six main types of content: communication, entertainment, situational, news, sales, and reputation. The study analyzes changes in content plan structure of companies providing various categories of consumer goods in 2022. The reviewed companies operate in Russia, have official accounts VK and actively interact with users. These companies’ activity on VK has been reviewed and analyzed and trends in various types of content placement considered. The regularities in companies’ content plan change and types of prevailing content for 2022 have been highlighted. The article concludes that Russian companies are facing a serious challenge related to the vacated market niches due to a number of foreign brands market withdrawal. Companies that change their content plan in the direction of active interaction with users and effective use of available social network opportunities will have a clear advantage over those ones that continue to focus their efforts on Western resources, access to which is significantly hindered, and advertising placement and use of paid promotion tools are illegal.